O-GlcNAc impacts mitophagy via the PINK1-dependent pathway - Alghusen, Ibtihal M.; Carman, Marisa S.; Wilkins, Heather M.; Strope, Taylor A.; Gimore, Caleb; Fedosyuk, Halyna; Shawa, Jad; Ephrame, Sophiya John; Denson, Aspin R.; Wang, Xiaowan; Swerdlow, Russell H.; Slawson, Chad (Frontiers in Aging Neuroscience, 2024)
The accumulation of dysfunctional mitochondria is an early feature of Alzheimer Disease (AD). The impaired turnover of damaged mitochondria increases reactive oxygen species production and lowers ATP generation leading to cellular toxicity and neurodegeneration. Interestingly, AD exhibits a disruption in the global posttranslational modification β-N-acetylglucosamine (O-GlcNAc). O-GlcNAc is a ubiquitous single sugar modification found on nuclear, cytoplasmic, and mitochondrial proteins. Cells maintain a homeostatic level of O-GlcNAc by cycling the addition and removal of the sugar by O-GlcNAc transferase (OGT) or O-GlcNAcase (OGA) respectively.We used patient-derived induced pluripotent stem cells, a transgenic mouse model of AD, SH-SY5Y neuroblastoma cell-lines to examine the effect of sustained O-GlcNAcase inhibition by Thiamet-G (TMG) or OGT deficiency on mitophagy using biochemical analyses.Results: Here, we established an essential role for O-GlcNAc in regulating mitophagy (mitochondria-selective autophagy). Stimulating mitophagy using Urolithin A (UA) decreases cellular O-GlcNAc and elevates mitochondrial O-GlcNAc. Sustained elevation in O-GlcNAcylation via pharmacologically inhibiting OGA using Thiamet G (TMG) increases mitochondrial level of mitophagy protein PINK-1 (PTEN-induced kinase-1) and autophagy-related protein light chain 3 (LC3). Moreover, we detected O-GlcNAc on PINK-1 and TMG increases its O-GlcNAcylation level. Conversely, decreasing cellular O-GlcNAcylation by knocking down OGT decreases both PINK1 and LC3 protein expression. Mitochondria isolated from CAMKII-OGT-KO mice also had decreased PINK1 and LC3. Moreover, human brain organoids treated with TMG showed significant elevation in LC3 compared to control. However, TMG treated AD organoids showed no changes in LC3 expression.Collectively, these data demonstrate that O-GlcNAc plays a crucial role in activation and progression of mitophagy, and this activation is disrupted in AD.